Exploring the role of diosgenin in modulating RUNX1 and HIPK2 transcription to mitigate Primary Sjögren's Syndrome - Yiwei Pan; Lunquan Wei; Han Liu; Fang Wang; Minhua Wang; Meijia Li; Pengfei Cheng; Xing Yan (Immunobiology)
Background: Primary Sjögren's Syndrome (pSS) is a chronic autoimmune disease characterized by inflammation of the exocrine glands, resulting in symptoms like dry mouth and eyes. Despite existing symptomatic treatments, underlying immune dysregulation remains undefined. Diosgenin, a steroidal saponin derived from Mai Dong, shows potential in modulating immune responses, but its mechanism in pSS remains underexplored. Methods: This study investigated the immunomodulatory effects of diosgenin on pSS using in vivo and in vitro approaches. In vivo, salivary flow rate measurement, histological analysis, quantitative real-time PCR (qRT-PCR), flow cytometry and Western blot were performed on NOD/ShiLtJ mice after treatment with diosgenin at various concentrations. In vitro, CD4+ T cells isolated from these mice were treated with diosgenin to assess T cell differentiation via flow cytometry, qRT-PCR, Enzyme-Linked Immunosorbent Assay (ELISA) and Western blot, where Homeodomain-Interacting Protein Kinase 2 (HIPK2) overexpression and Runt-associated transcription factor 1 (RUNX1) knockdown were manipulated. Results: Diosgenin stabilized salivary flow rates, reduced lymphocytic infiltration and inflammatory cytokines levels, upregulated RUNX1 and downregulated HIPK2, which modified T cell dynamics by promoting regulatory T cells (Treg) and reducing T helper 17 (Th17) populations. However, HIPK2 overexpression reversed the effects of diosgenin on inhibiting Th17 differentiation and inflammatory cytokines levels and promoting RUNX1 level. Additionally, RUNX1 knockdown also offset the suppressive effects of diosgenin on Th17 differentiation, inflammatory cytokine levels, and HIPK2 expression. Conclusion: Diosgenin effectively impacts immune responses in pSS, potentially through the modulation of RUNX1 and HIPK2 transcription factors, leading to a reduction in Th17-mediated inflammation.